Baseline Plasma Zinc and Risk of First Stroke in Hypertensive Patients: A Nested Case-Control Study. Issue 11 (November 2019) - Zhang, Jingping; Cao, Jingjing; Zhang, Yuanyuan; Li, Huan; Zhang, Hao; Huo, Yong; Li, Jiaang; Liu, Xiangyi; Wang, Xiaobin; Qin, Xianhui; Xu, Xiping
Abstract : Background and Purpose—: We aimed to examine the relation of baseline plasma zinc with the risk of first stroke and investigate any possible effect modifiers in hypertensive patients. Methods—: The study population was drawn from the CSPPT (China Stroke Primary Prevention Trial), using a nested case-control design, including 599 first stroke cases and 599 matched controls. Results—: Compared with participants with baseline plasma zinc <106.9 μg/dL (median), a significantly lower risk of first hemorrhagic stroke was found in those with plasma zinc ≥106.9 μg/dL (multivariate-adjusted odds ratio, 0.45; 95% CI, 0.21–0.94). Furthermore, the inverse plasma zinc-first hemorrhagic stroke association was significantly stronger in participants with body mass index ≥25.0 kg/m 2 or plasma copper <100.1 μg/dL at baseline ( P interaction <0.05 for both variables). However, there was no significant association between plasma zinc and first ischemic stroke (<103.3 versus ≥103.3 μg/dL [median]; multivariate-adjusted odds ratio, 1.16; 95% CI, 0.83–1.61). Conclusions—: In this sample of hypertensive patients, we found a significant, inverse association between plasma zinc and first hemorrhagic stroke. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00794885. Abstract : Supplemental Digital Content is available in the text.